From outreach to equity : innovative models of library policy and practice - Osborne, Robin, 1954- (American Library Association, 2004)
The many assumptions about current library outreach services - that they're off-site, depend on special funding, and are administered by specific staff - no longer reflect the realities of providing equitable library services to the audiences who most need them. This guide answers both "why" and "how."